Prognostic Value of Procalcitonin for Morbidity and Mortality in Patients after Cardiac Surgery. (26th July 2021) - Amouzeshi, Ahmad; Abedi, Farshid; Zardast, Mahmoud; Rezaeian Bilondi, Yaser; Amouzeshi, Zahra
Abstract : Background . The increased serum procalcitonin (PCT) level in cardiac patients is known as a sign of postoperative complications. Objective . Considering the importance of predicting the incidence of both complications and mortality caused by coronary artery bypass graft (CABG) surgery, this study was conducted to determine the serum PCT level and its relationship with one-year morbidity and mortality among CABG patients. Methods . This descriptive-analytical study was performed on 100 patients who underwent CABG surgery in Vali-e-Asr Hospital of Birjand, Iran. They were selected by a census sampling method from March 2014 to March 2015. The Elecsys BRAHMS PCT kit (Roche Company) was then used to measure the patients' serum PCT level. The required data were collected using the patients' medical records and telephone interviews with the patient or his/her relatives by passing one year from their discharge. The outcomes of this study comprised of mortality and morbidity causes (e.g., dysrhythmia, infection, and stroke). The data were then analyzed in SPSS version 16 by Mann–Whitney, chi-squared, and Fisher exact tests. Results . The postoperative serum PCT level is significantly correlated with sternum wound infection (p = 0.001 ), packed cells (PC) transfusion (p = 0.003 ), and death (p = 0.003 ). In addition, a significant relationship was found between dyslipidemia and hypertension and early mortality rate in patients with high levels of PCT. Of note, risk-adjusted death did not differ significantly between the serum PCT levels after one year (RR, 0.068; 95% CI 0.008–0.566). Conclusion . Higher PCT serum levels in CABG patients are associated with the increased early mortality rate, sternum wound infection, and PC transfusion. Additionally, the other factors associated with mortality in the patients under study included dyslipidemia and hypertension.